A dimmable flyback high power LED driver with constant-current control - Carlos, Roberto Emmanuel A. (2009.)
Light Emitting Diodes (LEDs) are the state-of-the-art light sources of today. New power LEDs have a high luminous efficacy that exceeds that of current lighting sources such as fluorescent lamps. However, the brightness of a single LED is not enough for general illumination. An LED lighting fixture used for universal lighting usually consists of a string of LEDs connected in series. An LED string must be supplied by switch-mode power supply drivers and not via series resistors for reasons of efficiency and control. An offline flyback converter with constant-current output and dimming control was created to drive the LED string. The flyback topology was chosen because of its high efficiency when operated below 100W. The driver supplies constant current to the LED array to produce a stable, consistent illumination level. The output constant current can also be varied to change the output luminance of the LED array.
Thesis (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Light emitting diodes; Electric current converters; Flyback converter; Flyback converter topologies; LED driver